2004
DOI: 10.1111/j.1365-201x.2004.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal autoregulation in P2X1 knockout mice

Abstract: Autoregulation of renal blood flow is an established physiological phenomenon, however the signalling mechanisms involved remain elusive. Autoregulatory adjustments in preglomerular resistance involve myogenic and tubuloglomerular feedback (TGF) influences. While there is general agreement on the participation of these two regulatory pathways, the signalling molecules and effector mechanisms have not been identified. Currently, there are two major hypotheses being considered to explain the mechanism by which T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…It was further proposed that the released ATP itself through activation of purinergic P2 receptors triggers an increase in cytosolic Ca 2ϩ in the extraglomerular mesangium cells and/or the smooth muscle cells of the afferent arteriole, and thus ATP acts as the principal mediator of TGF (22,239). Even though substantial evidence points to a role of ATP and P2X1 receptors in renal autoregulation (142,239), no data have been published that indicate a direct role of a P2 receptor in the TGF response, such as studies with selective receptor antagonists or in knockout mice demonstrating inhibition of macula densa-dependent control of SNGFR. Moreover, Ren et al (279) microperfused rabbit afferent arterioles and attached macula densas simultaneously in vitro and found that adding the P2 purinergic receptor inhibitor suramin to both arteriole lumen and bath did not significantly inhibit the TGF response.…”
Section: Adenosine Is a Mediator Of Tgfmentioning
confidence: 99%
“…It was further proposed that the released ATP itself through activation of purinergic P2 receptors triggers an increase in cytosolic Ca 2ϩ in the extraglomerular mesangium cells and/or the smooth muscle cells of the afferent arteriole, and thus ATP acts as the principal mediator of TGF (22,239). Even though substantial evidence points to a role of ATP and P2X1 receptors in renal autoregulation (142,239), no data have been published that indicate a direct role of a P2 receptor in the TGF response, such as studies with selective receptor antagonists or in knockout mice demonstrating inhibition of macula densa-dependent control of SNGFR. Moreover, Ren et al (279) microperfused rabbit afferent arterioles and attached macula densas simultaneously in vitro and found that adding the P2 purinergic receptor inhibitor suramin to both arteriole lumen and bath did not significantly inhibit the TGF response.…”
Section: Adenosine Is a Mediator Of Tgfmentioning
confidence: 99%
“…As discussed in more detail by Inscho, the kidney is a highly efficient autoregulatory organ and it is generally accepted that the TGF mechanism is responsible, at least in part, for this behaviour [90][91][92][93]. Thus, in response to an increase in blood pressure, there would be a transient elevation in GFR, leading to increased tubular flow into the proximal tubule.…”
Section: Atp As a Mediator Of Tgfmentioning
confidence: 99%
“…A more direct means of assessing the role of ATP in autoregulatory responses is the in vitro bloodperfused juxtamedullary nephron preparation. Inscho and coworkers [49,82,87,88,91] found that pressure-induced afferent arteriolar vasoconstriction was attenuated during pharmacological blockade of P2 receptors with suramin, PPADS or the more selective blocker NF-279. Desensitisation of P2 receptors also inhibited pressure-induced autoregulatory adjustments in afferent arteriolar diameter.…”
Section: Atp As a Mediator Of Tgfmentioning
confidence: 99%
“…Autoregulation of renal blood flow (RBF) has long been recognized (153,202). It has since been extensively studied and is well characterized under steady-state conditions as summarized in many excellent review articles (78,87,123,139,168,199). It is thought today, that RBF autoregulation is based on two mechanisms, the myogenic response (MR) and the tubuloglomerular feedback (TGF).…”
mentioning
confidence: 99%